Livelihood improvement through integrated farming system - Kulkarni, Shyamrao; Sharanappa, Prakash (Indian Farming, 2018)
A computer personnel (Kavita Umashankar) turned in to a farm-women with her 8 acres of land. She took challenge to develop her farm into a model farm. After all land development activities, she thought of planting horticulture crops with view of that they would give sustainable income in near future, and then divided whole land into 6 plots, started planting of different plantation crops. Block-wise different planting was done during 2008-09. During 2015’ farmer produced 30,000 sandalwood seedlings from which she earned ` 9,00,000 by selling sandalwood seedlings, which is gaining enormous response from farming community. By looking into her involvement in the field, management and dissemination skill. University of Agricultural Sciences, Raichur awarded her as Best Farm-Women at Krishi mela during 2013.